Study and application of temporary plugging agent for temporary plugging acid fracturing in ultra-deep wells of Penglai gas field - Wang, Yang; Fan, Yu; Chen, Weihua (Frontiers in Physics, 2023)
The burial depth of Penglai gas field reservoir in the Sichuan Basin of China exceeds 7000m, and the reservoir temperature is 160℃. Penglai gas field belongs to the fractured reservoir, and there are many natural fractures distributed in the reservoir. Natural fractures are not only the storage place of natural gas, but also the transportation channel of natural gas. Gas wells mainly increase natural gas production through acid fracturing. In the early stage, Penglai Gas Field mainly used gelled acid fracturing technology to create an artificial fracture in the reservoir by injecting a large amount of acid fluid. However, the stimulation range of gelled acid fracturing is very small. After acid fracturing, gas wells can only produce 120000 cubic meters of natural gas per day. To obtain higher natural gas production, this paper proposes a multi-stage temporary acid fracturing technology that can greatly improve the effect of acid fracturing. The temporary plugging agent for acid fracturing has been developed to meet the high-temperature requirements of the Penglai gas field. Based on the simulation of fracture propagation, the feasibility of acid fracturing expansion of natural fractures in the Penglai Gas Field is clarified. Fiber and granular temporary plugging agents that meet the plugging strength greater than 20MPa are selected by using the dynamic temporary plugging instrument. MultiFracS software is used to optimize the multi-stage temporary acid fracturing process parameters. The research results in this paper have been applied to wells PS101, PS102, and PS103. After fracturing, compared with the gelling acid fracturing, the natural gas production has increased by more than three times, and the multi-stage temporary plugging acid fracturing has achieved a very good stimulation effect.